2011
DOI: 10.1002/lary.21450
|View full text |Cite
|
Sign up to set email alerts
|

Viagra deafness—Sensorineural hearing loss and phosphodiesterase‐5 inhibitors

Abstract: There is increasing evidence that PDE-5 inhibitors may induce sensorineural hearing loss via plausible physiological mechanisms. There needs to be more awareness of this disabling side effect among healthcare professionals responsible for prescribing this drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 31 publications
1
37
0
2
Order By: Relevance
“…12,22 Adverse effects are generally mild, 12 although vision-threatening ocular complications and hearing loss have been reported. 22,27 Arozarena et al recently found that PDE5A inhibition by sildenafil induces invasion of melanoma in vitro . 8 Moreover, the oncogenic BRAF mutation was shown to down-regulate PDE5A through the RAS/RAF/MEK/ERK signaling pathway and PDE5A down-regulation can stimulate a dramatic increase in melanoma cell contractility and invasion, despite causing a slight decrease in proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…12,22 Adverse effects are generally mild, 12 although vision-threatening ocular complications and hearing loss have been reported. 22,27 Arozarena et al recently found that PDE5A inhibition by sildenafil induces invasion of melanoma in vitro . 8 Moreover, the oncogenic BRAF mutation was shown to down-regulate PDE5A through the RAS/RAF/MEK/ERK signaling pathway and PDE5A down-regulation can stimulate a dramatic increase in melanoma cell contractility and invasion, despite causing a slight decrease in proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Khan et al [26] published a report based on data provided by pharmacovigilance agencies Europe, the Americas, East Asia and Australasia, and on published reports. The authors identified among PDE5 inhibitor users 47 cases of sensorineural hearing loss, most of them unilateral.…”
Section: Phosphodiesterase-5 (Pde5) Inhibitorsmentioning
confidence: 99%
“…Um estudo experimental sul-coreano de 2008 em ratos mostrou os potenciais efeitos de perda auditiva com uso prolongado e de altas doses de inibidores de PDE-5 [77][78][79] . O mesmo ocorreu em um estudo clínico de 2009 [80] .…”
Section: -Inibidores Da Pde-5 E Perda Auditivaunclassified
“…Um estudo de coorte de 2010, avaliando 11.525 homens, com 40 anos ou mais, por 2 anos, mostrou que a perda auditiva foi duas vezes mais comum entre utilizadores dos inibidores de PDE-5 82 . Mais estudos a respeito são necessários, mas alguma relação já é observada e precisa ter a atenção médica 78,80,81 . Quarenta e sete casos de perda de audição súbita relacionada aos inibidores da PDE-5 foram investigados por agências de farmacovigilância.…”
Section: -Inibidores Da Pde-5 E Perda Auditivaunclassified